Effects of Child Maltreatment, Cumulative Victimization Experiences, and Proximal Life Stress on Adult Outcomes of Substance Use, Mental Health Problems, and Antisocial Behavior, 2 Pennsylvania counties, 1976-2010 - Herrenkohl, Todd ([Verlag nicht ermittelbar], 2021)
The study investigates protective factors for maltreated children and predictors of self-reported crime desistence among maltreated and multiply victimized children. Data are from the Lehigh Longitudinal Study, a prospective investigation of children and families that began in the 1970s. The original sample was comprised of 457 children and their families. Over 80 percent of the children, now adults, were most recently assessed in 2010, at an average of 36 years, using a comprehensive, interviewer-administered survey. Data on child maltreatment and related risk and protective factors were collected much earlier, beginning when participants were preschoolers, 18 months to 6 years of age. Childhood data are from multiple sources, including child welfare case observations of parents and children, school records, and parent and adolescent surveys. Data collected during adolescence and adulthood offer detailed accounts of the psychosocial adjustment and well-being of participants and their families at later life stages, ongoing experiences of abuse and victimization, self-reported crime and antisocial behavior, and protection and resilience.